Developing the interbank payment system: Efficiency of public versus private investments - Karlo Kauko (Bank of Finland, 1998)
In this paper a game theoretic duopoly model is developed to analyse the development of an interbank payment system.There are two competing banks in the model, and payment services offered to the public are among their main products.The customer of the larger bank uses mainly intrabank payment services; these services are assumed to be of high quality.This creates a so-called network externality, meaning that many customers prefer to use the large bank for quality reasons.The development of interbank payment systems reduces the significance of this factor and hence benefits the small bank.A big bank has a sufficient incentive to develop the system only if a fee is charged for using payment systems.The role for public investment depends critically on the pricing of payment services.If banks offer payment services free of charge, their incentives to develop the system are strongly biased, and it would be efficient for the central bank to have an active role in developing the system.If instead payment services are directly priced, eventual distortions are much less serious, and the role of the central bank need not be as prominent.
URN:NBN:fi:bof-20140807225
Keywords: G18; G21; L13; 330; banks; payments systems; network externality; duopoly